What Makes Mental Modeling Difficult? Normative Data for the Multidimensional Relational Reasoning Task - Cortes, Robert A.; Weinberger, Adam B.; Colaizzi, Griffin A.; Porter, Grace F.; Dyke, Emily L.; Keaton, Holly O.; Walker, Dakota L.; Green, Adam E. (Frontiers in Psychology, 2021)
Relational reasoning is a complex form of human cognition involving the evaluation of relations between mental representations of information. Prior studies have modified stimulus properties of relational reasoning problems and examined differences in difficulty between different problem types. While subsets of these stimulus properties have been addressed in separate studies, there has not been a comprehensive study, to our knowledge, which investigates all of these properties in the same set of stimuli. This investigative gap has resulted in different findings across studies which vary in task design, making it challenging to determine what stimulus properties make relational reasoning – and the putative formation of mental models underlying reasoning – difficult. In this article, we present the Multidimensional Relational Reasoning Task (MRRT), a task which systematically varied an array of stimulus properties within a single set of relational reasoning problems. Using a mixed-effects framework, we demonstrate that reasoning problems containing a greater number of the premises as well as multidimensional relations led to greater task difficulty. The MRRT has been made publicly available for use in future research, along with normative data regarding the relative difficulty of each problem.